PENGARUH KETERIKATAN KERJA TERHADAP KETERLIBATAN KERJA DAN KINERJA DENGAN DIMEDIASI FAKTOR KEPERCAYAAN TERHADAP ATASAN - Alvinda Rian Jannatin; Dewita Puspawati (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
In order for the organization to run smoothly, it is necessary to have a strong work engagement of human resources in their duties and work. Employee engagement relates to the level of commitment and involvement of employees to the organization and its values. The purpose of this study was to determine the effect of work engagement on trust in superiors. To determine the effect of trust in superiors on work engagement, to determine the effect of trust in superiors on performance, to determine the effect of work engagement on work involvement mediated by trust in superiors and to determine the effect of work involvement on performance mediated by trust in superiors. This research using a quantitative survey. The results in this study are work engagement has a significant effect on trust in superiors, Trust in superiors has no effect on work involvement, Trust in superiors has a significant effect on performance, Work engagement has no effect on job involvement mediated by trust factor to superiors. Work engagement has a significant effect on performance by mediating trust factor to superiors. The Civil Registry (Disdukcapil) of Sragen Regency further improves and evaluates the level of employee work involvement to make it even better